Sentiment Analysis of Indonesian X Users in the Israeli Product Boycott Movement - Waluyo, Bambang Dwi; Aldi Istihsan, Muhammad (PERSPEKTIF, 2025)
This study examines the sentiment of Indonesian users on the social media platform X regarding the boycott movement of Israeli products. The movement, rooted in the global Boycott, Divestment, and Sanctions (BDS) campaign, reflects strong pro-Palestinian sentiment in Indonesia. Using sentiment analysis techniques, including VADER, 4,002 tweets from October 2023 to August 2024 were analyzed to classify sentiments as positive, negative, or neutral. Results reveal that 63% of tweets express negative sentiment, supporting the boycott movement; 33% indicate positive sentiment, opposing the movement; and 4% remain neutral. Peaks in tweet activity coincide with significant events, such as the Indonesian Ulema Council's fatwa and geopolitical developments. The study also explores factors influencing public engagement, including hashtag usage, timing, and influencer participation. Findings highlight the role of social media in shaping public opinion and mobilizing collective action while contributing to academic discourse on digital platforms as arenas for cultural and political expression.